Intelligent Data Analysis and Applications Proceedings of the Second Euro-China Conference on Intelligent Data Analysis and Applications, ECC 2015 - Abraham, Ajith; Jiang, Xin Hua; Snášel, Václav; Pan, Jeng-Shyang (Advances in Intelligent Systems and Computing, 2015)
This volume of Advances in Intelligent Systems and Computing contains accepted papers presented in the main track of ECC 2015, the Second Euro-China Conference on Intelligent Data Analysis and Applications. The aim of ECC is to provide an internationally respected forum for scientific research in the broad area of intelligent data analysis, computational intelligence, signal processing, and all associated applications of AIs. The second edition of ECC was organized jointly by VSB - Technical University of Ostrava, Czech Republic, and Fujian University of Technology, Fuzhou, China. The conference, organized under the patronage of Mr. Miroslav Novak, President of the Moravian-Silesian Region, took place in late June and early July 2015 in the Campus of the VSB - Technical University of Ostrava, Czech Republic.